Sleep Disorders (Homoeopathy for All, 2024)
Sleep is a natural and essential  state of rest for the body and mind.  It is characterized by reduced  consciousness, decreased sensory  activity, and limited movement.  Sleep plays a crucial role in several  aspects of our lives. During sleep,  the body repairs and rejuvenates  tissues, muscles, and organs. It's  a time for the body to recover  from daily wear and tear. Quality  sleep supports the immune system,  helping the body defend against  illnesses and infections. Adequate  sleep is linked to better emotional  regulation, mental well-being, and  overall quality of life.
Keywords: natural; characterized; regulation